Bonding at Particle Contacts - Suyud Rusai Karyasuparta (Jurnal Teknik Sipil, 2003)
Abstract. This investigation deals with the behavior of cohesive bonding at particle contacts in soil. Direct measurement of cohesive strength at sliding contacts between particles of soil has not been accomplished. An indirect method is used in this study to estimate average contact cohesion from measurement of total strength of soil specimens. Two types of materials were tested; Ottawa sand and crushed quartz, with two different relative densities, 25 and 75 percents; each material was tested with four different cement contents, 0, 2, 4, and 6 percents of cement by weight. Adding cement was to create controlled cohesion to the contacts between particles. The results of 118 Consolidated Drained Triaxial compression tests on sand-cement specimens were analyzed, and the model by Hardin (1985) was used to isolate cohesive and frictional bonding in cohesive materials. This model considers two basic mechanism of strength of soils, by considering bonding at particle contacts and kinematics of particle movement within an element of deforming soil. The result shows that the dimensionless contact cohesion is linearly related to cement content for sand with relative density 25 percent, and is nonlinear for sand with relative density 75 percent. Dimensionless contact cohesion decreases with increasing relative density for cement content 2 and 4 percents, but it increases with increasing relative density for 6 percent cement content. Dimensionless contact cohesion is larger in rounded material compared with in angular material.Abstrak. Penelitian ini adalah mengenai perilaku dari ikatan kohesif pada kontak antar butir tanah. Pengukuran langsung kohesi pada bidang geser kontak antara butir-butir tanah, belum pernah dilakukan. Suatu cara tidak langsung dipakai dalam studi ini, untuk memprakirakan kohesi kontak (pada bidang geser antara 2 butir) ratarata, dari pengukuran tegangan-tegangan total pada benda uji tanah. Dua jenis material pasir diuji; yaitu pasir Ottawa dan crushed quatz (quartz tumbuk), dengan 2 nilai relative density yaitu 25% dan 75%; tiap material diuji dengan 4 kadar semen yang berbeda yaitu 0%, 2%, 4% dan 6% berat semen. Penambahan semen pada pasir tersebut, adalah untuk menciptakan kohesi yang dapat diatur, pada bidang kontak. Hasil uji Consolidated Drained Tiaxial compression pada 118 benda uji pasir bersemen diatas, dianalisis, dan sebuah model dari Hardin (1985), dipakai untuk mengisolasi ikatan kohesi dan ikatan geser pada material kohesif. Model tersebut  memperhatikan dua mekanisme dasar dari kekuatan tanah, dengan memperhatikan ikatan pada kontak antara butir dan kinematik dari pergerakan partikel dalam sebuah elemen dari tanah yang berdeformasi. Hasilnya memperlihatkan bahwa kohesi kontak tak berdimensi berhubungan linier terhadap kadar semen, untuk pasir dengan relative density 25%, dan tidak linier untuk pasir dengan relative density 75%. Kohesi kontak tak berdimensi berkurang dengan bertambahnya relative density, untuk kadar semen 2 dan 4%, tetapi bertambah besar dengan naiknya relative density, untuk kadar semen 6%. Kontak kohesi tak berdimensi lebih besar pada pasir yang rounded dibanding dengan pada pasir yang angular. Wurbs, Ralph A., 1996, "Modeling & Analysis of Reservoir System Operations", PTR Prentice Hall.